Lexicalisation of temperature concepts in Gbaya,(an Ubanguian language of C.A.R.) - (:unkn) unknown (My University, 2015)
The chapter provides a systematic description of the temperature terms found in Gbaya, an Ubanguian language spoken in Central Africa. Gbaya has very few nouns and verbs dedicated to temperature but many adjectives – verbal adjectives and ideophonic adjectives. I first present the word classes and the syntactic constructions involved in expressing temperature and examine the different systems of temperature terms with respect to the following five domains: weather conditions, body-parts, the house, food, and water. I then indicate the main cultural specificities or metaphors used to refer to temperature. In conclusion, the domain of temperature is organised opposing two levels WARM / COLD and it is only by juxtaposing the many lexical and syntactic possibilities that an understanding of ways of expressing temperature emerges.
Keywords: African Research